PERBEDAAN EFEKTIVITAS KOMBINASI METFORMIN DAN SULFONILUREA DENGAN KOMBINASI METFORMIN DAN PENGHAMBAT DPP-IV DALAM MENGONTROL HbA1c PASIEN DM TIPE 2 - Camelia Fasya Zhafira Arethusa (2021)
The Indonesian Ministry of Health states that the prevalence of diabetes mellitus (DM) is 20.4 million people and it is estimated that in 2030 it will reach 21.3 million people. The metformin group is currently the most widely prescribed drug for initial therapy as monotherapy. Based on the management algorithm for T2DM, patients who had been on monotherapy for 3 months but could not meet HbA1c <7%, were given a combination of 2 drugs with different mechanisms of action. The sulfonylurea group is one of the drugs that is often used as a combination drug with metformin, but the combination of these drugs often gives a hypoglycemic effect, while the DPP-IV inhibitor class, which is a new class, has also begun to be used in combination with metformin due to few and no side effects. cause hypoglycemia. The aim of this study was to understand the differences in the effectiveness of the combination of metformin and a sulfonylurea with a combination of metformin and a DPP-V inhibitor in controlling HbA1c in T2DM patients using a systemic literature review method. Journals were assessed using a review instrument developed by the National Heart, Lung and Blood Institute (NHLBI) and the Research Triangle Institute International. This study proves that there is no difference in the effectiveness of the two combinations, there is even one research journal which states that there is a difference in the effectiveness of the drug combination, where DPP-IV inhibitors provide long-term glycemic control.